2022
DOI: 10.3389/fphys.2022.1048208
|View full text |Cite
|
Sign up to set email alerts
|

Resistance selection of triflumezopyrim in Laodelphax striatellus (fallén): Resistance risk, cross-resistance and metabolic mechanism

Abstract: The risk assessment and resistance mechanisms of insecticide resistance are critical for resistance management strategy before a new insecticide is widely used. Triflumezopyrim (TFM) is the first commercialized mesoionic insecticide, which can inhibit nicotinic acetylcholine receptor with high-performance against the small brown planthopper (SBPH), Laodelphax striatellus (Fallén). In our study, the resistance of SBPH to TFM increased 26.29-fold, and the actual heritability of resistance was 0.09 after 21 gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The results suggested that CYP417A2 could positively regulate the tolerance of SBPH to triflumezopyrim. Previous researchers have not found the cross‐resistance between triflumezopyrim and other neonicotinoid insecticides 9,38 . But CYP417A2 protein can effectively degrade imidacloprid in SBPH 18 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results suggested that CYP417A2 could positively regulate the tolerance of SBPH to triflumezopyrim. Previous researchers have not found the cross‐resistance between triflumezopyrim and other neonicotinoid insecticides 9,38 . But CYP417A2 protein can effectively degrade imidacloprid in SBPH 18 .…”
Section: Discussionmentioning
confidence: 93%
“…Previous researchers have not found the cross-resistance between triflumezopyrim and other neonicotinoid insecticides. 9,38 But CYP417A2 protein can effectively degrade imidacloprid in SBPH. 18 Therefore, there is a risk of cross-resistance between triflumezopyrim and imidacloprid through CYP417A2 protein in SBPH.…”
Section: Discussionmentioning
confidence: 99%